(untitled) (Academicia Globe: Inderscience Research, 2023)
The article deals with the attitude of the conservative approach in bioethics to the problems of bioethics. Conservative bioethics relies more on traditions, values, moral principles and appeals to the sanctity of human life. A conservative approach to bioethics denounces biomedical interference with nature and human reproduction, artificial insemination, embryo transfer, in vitro fertilization and surrogacy. The goal of conservative bioethics is respect for human life, health and eternal values, preservation of traditions and values in matters of bioethics.